Utility of high-resolution accurate MS to eliminate interferences in the bioanalysis of ribavirin and its phosphate metabolites. (August 2012) - Wei, Cong; Grace, James E; Zvyaga, Tatyana A; Drexler, Dieter M
Background: The polar nucleoside drug ribavirin (RBV) combined with IFN-α is a front-line treatment for chronic hepatitis C virus infection. RBV acts as a prodrug and exerts its broad antiviral activity primarily through its active phosphorylated metabolite ribavirin 5´-triphosphate (RTP), and also possibly through ribavirin 5´-monophosphate (RMP). To study RBV transport, diffusion, metabolic clearance and its impact on drug-metabolizing enzymes, a LC–MS method is needed to simultaneously quantify RBV and its phosphorylated metabolites (RTP, ribavirin 5´-diphosphate and RMP). In a recombinant human UGT1A1 assay, the assay buffer components uridine and its phosphorylated derivatives are isobaric with RBV and its phosphorylated metabolites, leading to significant interference when analyzed by LC–MS with the nominal mass resolution mode.Results: Presented here is a LC–MS method employing LC coupled with full-scan high-resolution accurate MS analysis for the simultaneous quantitative determination of RBV, RMP, ribavirin 5´-diphosphate and RTP by differentiating RBV and its phosphorylated metabolites from uridine and its phosphorylated derivatives by accurate mass, thus avoiding interference.Conclusion: The developed LC–high-resolution accurate MS method allows for quantitation of RBV and its phosphorylated metabolites, eliminating the interferences from uridine and its phosphorylated derivatives in recombinant human UGT1A1 assays.